2009
DOI: 10.1158/1055-9965.epi-09-0250
|View full text |Cite
|
Sign up to set email alerts
|

Stomach Carcinoma Incidence Patterns in the United States by Histologic Type and Anatomic Site

Abstract: Background: Using data from the U.S. National Cancer Institute's Surveillance, Epidemiology, and End Results program, we analyzed stomach carcinoma incidence patterns by both histologic type and anatomic site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
136
3
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(157 citation statements)
references
References 35 publications
14
136
3
4
Order By: Relevance
“…12 Male predominance was lost in patients younger than 30 years of age. Similar finding was observed by a study done by Wu H et al 13 According to the classification proposed by Lauren in 1965, gastric cancer has two histologic subtypes: Intestinal and Diffuse. 14 The most common type of gastric cancer in this study was intestinal type followed by mixed type and diffuse type.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…12 Male predominance was lost in patients younger than 30 years of age. Similar finding was observed by a study done by Wu H et al 13 According to the classification proposed by Lauren in 1965, gastric cancer has two histologic subtypes: Intestinal and Diffuse. 14 The most common type of gastric cancer in this study was intestinal type followed by mixed type and diffuse type.…”
Section: Discussionsupporting
confidence: 90%
“…Wu H et al in his study found 74% to be intestinal type and 16% diffuse type which concord with this study. 13 In this study diffuse type adenocarcinoma was seen in younger patients in comparison with intestinal-type cancer. Lauren himself observed a stronger male preponderance and older age at diagnosis for intestinal-typecancer than for diffusetype cancer 14 , which was corroborated by HanaiA et al 15 Prognostic factors on survival includes tumor location, depth of penetration, lymph node status, Lauren classification, histological grade, micro vessel invasion, type ofresection performed, and use of postoperative chemotherapy and radiation therapy.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Recent studies have reported a continuing rise in the incidence of adenocarcinoma of the gastroesophageal junction (GEJ) despite a decline in the overall incidence of gastric carcinoma in Western countries [1,2]. Adenocarcinoma of the GEJ is defined as carcinoma centered within 5 cm of the anatomic GEJ, which is further classified into three distinct entities (types I, II, and III) according to the anatomic location of the tumor center [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, lower esophageal cancers and those involving the GEJ and proximal stomach have increased rapidly in incidence in Western countries [7]. As tumor site influences the operative approach required, this results in Western patients frequently requiring more invasive surgery.…”
Section: How Geography and Surgery Impact On Treatment Choicementioning
confidence: 99%